CASUALTY REINSURANCE EXPOSURE RATING - Těšínská, Anna (2015)
The main aim of this thesis is a development of ILF curves that can be used in the insurance industry when pricing general third party liability on the Czech market. Based on available data there are first estimated size of loss distribution functions used for following generating process. From generated data the increased limit factors are estimated and with a usage of Riebesell's parameterization ILF curves are derived. A substantial part of the thesis is a compilation of literature and the expansion of the statistical approach for estimating fair ILFs based on these data. Besides, the basis for the curves derivation are chapters describing basic theoretical knowledge in the field of reinsurance - in particular, the description of the basic types of reinsurance contracts, as well as the most common methods of a pricing. There is the whole mechanism of curves derivation described; their own use is then demonstrated with the example based on pseudoreal data.